# 2003 AMC 10A Problems/Problem 5

## Problem

Let $d$ and $e$ denote the solutions of $2x^{2}+3x-5=0$. What is the value of $(d-1)(e-1)$? $\mathrm{(A) \ } -\frac{5}{2}\qquad \mathrm{(B) \ } 0\qquad \mathrm{(C) \ } 3\qquad \mathrm{(D) \ } 5\qquad \mathrm{(E) \ } 6$

## Solution

### Solution 1

Using factoring: $2x^{2}+3x-5=0$ $(2x+5)(x-1)=0$ $x = -\frac{5}{2}$ or $x=1$

So $d$ and $e$ are $-\frac{5}{2}$ and $1$.

Therefore the answer is $\left(-\frac{5}{2}-1\right)(1-1)=\left(-\frac{7}{2}\right)(0)=\boxed{\mathrm{(B)}\ 0}$

### Solution 2

We can use the sum and product of a quadratic (a.k.a Vieta): $(d-1)(e-1)=de-(d+e)+1 \implies\text{product}-\text{sum}+1 \implies \dfrac{c}{a}-\left(-\dfrac{b}{a}\right)+1 \implies \dfrac{b+c}{a}+1= \dfrac{5}{-5}+1=\boxed{\mathrm{(B)}\ 0}$

### Solution 3

By inspection, we quickly note that $x=1$ is a solution to the equation, therefore the answer is $(d-1)(e-1)=(1-1)(e-1)=\boxed{\mathrm{(B)}\ 0}$

The problems on this page are copyrighted by the Mathematical Association of America's American Mathematics Competitions. 